2007
DOI: 10.1111/j.1365-2745.2007.01287.x
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics in Digitalis purpurea: the interaction of disturbance and seed bank dynamics

Abstract: Summary1. Plant ecologists have long since realized that the persistence of many facultative biennial plants depends upon disturbance. However, we still have a limited knowledge of the population-level effects of disturbance, and the connection between adult and seed bank dynamics. 2. Using data from a 3-year demographic study combined with experimental gap-opening in a large population of Digitalis purpurea , we parameterized stochastic transition matrix models in 'disturbed' vs. 'undisturbed' areas. We simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 49 publications
3
25
1
Order By: Relevance
“…This presumably caused the short‐term stable vertical patterns of seeds in the soil that we observed. We also found clustered horizontal seed bank patterns, which is in line with the findings of Sletvold & Rydgren (2007) for the facultative biennial Digitalis purpurea . Indeed, all of the studies that have so far dealt with small‐scale spatial patterns of seed banks have reported clustered patterns (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This presumably caused the short‐term stable vertical patterns of seeds in the soil that we observed. We also found clustered horizontal seed bank patterns, which is in line with the findings of Sletvold & Rydgren (2007) for the facultative biennial Digitalis purpurea . Indeed, all of the studies that have so far dealt with small‐scale spatial patterns of seed banks have reported clustered patterns (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…This pattern contrasts with that of herbaceous species, for which seed survival and reproductive fecundity are the main factors responsible for population maintenance (Adams et al 2005, Menges & Quintana-Ascencio 2004, Silvertown et al 1993, Sletvold & Rydgren 2007. This fact can explain the low contribution of the processes such as the high fertility, abundant and permanent seed bank, and high seedling recruitment rate to the population dynamics of G. schottiana.…”
Section: Stagecontrasting
confidence: 67%
“…Grindeland et al. , 2005; Sletvold & Grindeland, 2007; Sletvold & Rydgren, 2007). However, only future plantings in the maternal environment can reveal whether differences reflect local adaptation, and also how fitness may be influenced by genotype × environment interactions.…”
Section: Discussionmentioning
confidence: 99%